DEVELOPMENT OF INTERACTIVE LEARNING APPLICATIONS USING ARTICULATE STORYLINE APPLICATIONS IN LIGHT SUBJECTS AND OPTICS SMP/MS - Dewi, Cindy Olanda; Maharani, Suci; Fikri, Ali (Universitas Negeri Medan, 2024)
The purpose of this research is to develop an Articulate Storyline-based learning application on Light and Optics so that it can help make learning more interesting and fun. With this application, it is hoped that students will be more interested and understand more about the material and concepts of Light and Optics. The type of research that the author uses is research and development R&D, which is the process used to develop and validate educational products. We conclude that the application that we make is interesting and the questions and sample questions that we provide already cover the material discussed and are easy to understand, it's just that there needs to be improvements or developments regarding design and color changes, icons that need to be aligned.Keywords: Articulate Storyline, Light and Optics, interesting.